Cross-Cultural Adaptation and Validation of the Jebsen-Taylor Hand Function Test in an Italian Population. (18th July 2016) - Culicchia, Greta; Nobilia, Marta; Asturi, Marilyn; Santilli, Valter; Paoloni, Marco; De Santis, Rita; Galeoto, Giovanni
Abstract : Objective . This paper describes the Italian translation and adaptation to the Italian culture of the original version of the Jebsen-Taylor hand function test and conveys the procedure for testing its validity and reliability. Design . The cultural adaptation process and validation were based on data from a group of people with no clinical evidence of disease or impairment of the upper limbs. The process required a forward and reverse translation in its original language. The scale obtained was reviewed by 8 experts in the field of psychometrics dealing with statistical methods that are useful for the behavioral and social sciences. The Italian adapted version of the JTHFT was then produced and validated. Participants . The test was submitted to 320 people with no clinical evidence of disease in order to test its acceptability and consistency. Results . The total time required to perform each subtest was 80.16 ± 43.13 seconds for the nondominant hand (NDH) and 49 . 97 ± 27 . 28 seconds for the dominant hand (DH). The internal consistency (assessed with Pearson's r ) and the reliability or the construct validity (assessed with Cronbach's alpha) are significative. Conclusions . This is the first study reporting the result of the translation, cultural adaptation, and validation protocols of the JTHFT in Italian. It provides a new tool for Italian professionals to measure the functionality of the hand in participants with various upper limb pathologies.